2013
DOI: 10.1007/s00436-013-3390-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of cyclophilin A from the hard tick Haemaphysalis longicornis on the growth of Babesia bovis and Babesia bigemina

Abstract: Haemaphysalis longicornis is known as one of the most important ticks transmitting Babesia parasites in East Asian countries, including Babesia ovata and Babesia gibsoni, as well as Theileria parasites. H. longicornis is not the natural vector of Babesia bovis and Babesia bigemina. Vector ticks and transmitted parasites are thought to have established unique host-parasite interaction for their survival, meaning that vector ticks may have defensive molecules for the growth control of parasites in their bodies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It also seems that cyclophilin A plays a role in tick-pathogen interactions. Maeda et al [199] suggested that cyclophilin A has regulatory role in the growth of Babesia parasites in H. longicornis ticks.…”
Section: Resultsmentioning
confidence: 99%
“…It also seems that cyclophilin A plays a role in tick-pathogen interactions. Maeda et al [199] suggested that cyclophilin A has regulatory role in the growth of Babesia parasites in H. longicornis ticks.…”
Section: Resultsmentioning
confidence: 99%
“…CypA has also demonstrated to be a powerful regulator of Ca 2+ in activated platelets (Elvers et al, 2012). Furthermore, CypA may play a role in the tick immune response to pathogens (Maeda et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…H. longicornis is easy to maintain and is widely used as a model tick to study pathophysiology in tick infestation33. To date, a number of bioactive molecules have been found in H. longicornis , and those products might be available for not only tick control but also for novel drug discovery in the veterinary and medical fields78343536. The experimental infection of ticks with pathogens is considered to be an attractive tool for studying tick-pathogen interaction56.…”
Section: Discussionmentioning
confidence: 99%
“…GIT (Nihon Pharmaceutical Co., Ltd., Tokyo, Japan) instead of bovine serum and M199 medium (Sigma-Aldrich, St. Louis, MO, USA) were used as the mixture with a ratio of 2:3. Fresh bovine blood was purchased from Nippon Bio-Test Laboratories Inc. (Tokyo, Japan) to prepare the red blood cells (RBCs)35. The culture was maintained at 37 °C with 5% oxygen and 5% carbon dioxide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation